2020
DOI: 10.3126/ijssm.v7i4.32475
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Perception on Corona Virus Disease 2019 (COVID-19) Among the General Public in Nepal

Abstract: The global pandemic of COVID-19 has created havoc worldwide with its high transmission rate. The vaccine and drugs are still under trial; thus, the only option is to break the chain of transmission of disease by imparting the knowledge and designing awareness campaigns to educate people about the risks and preventive measures of COVID-19.  This study was conducted to explore the knowledge and perception on health behaviors related to prevention along with addressing several myths and practices for COVID-19. An… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The studies investigated awareness, knowledge, behaviour change, implementation of health messages, etc. Many previous studies have shown social marketing mix strategies were applied in creating public awareness for positive health behaviour change (Abdulla et al, 2020;Bae et al, 2021;Banstola & Dhungana, 2021;Chisadza et al, 2021;Hossen et al, 2020;Hussain et al, 2021;Karn et al, 2020;Mongilala et al, 2020;Onuora et al, 2021;Rai et al, 2021;Sharma et al, 2021;Siddique et al, 2020;Soon et al, 2021;Tam et al, 2021;Tolga Şentürka, 2021;Waheed et al, 2020;Wardani et al, 2020) and the strategies components were product, price, place, promotion, public, policy, partnership, and purse strings. The interventions have significantly influenced the behaviour regarding using face masks and sanitizers and maintaining social distancing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies investigated awareness, knowledge, behaviour change, implementation of health messages, etc. Many previous studies have shown social marketing mix strategies were applied in creating public awareness for positive health behaviour change (Abdulla et al, 2020;Bae et al, 2021;Banstola & Dhungana, 2021;Chisadza et al, 2021;Hossen et al, 2020;Hussain et al, 2021;Karn et al, 2020;Mongilala et al, 2020;Onuora et al, 2021;Rai et al, 2021;Sharma et al, 2021;Siddique et al, 2020;Soon et al, 2021;Tam et al, 2021;Tolga Şentürka, 2021;Waheed et al, 2020;Wardani et al, 2020) and the strategies components were product, price, place, promotion, public, policy, partnership, and purse strings. The interventions have significantly influenced the behaviour regarding using face masks and sanitizers and maintaining social distancing.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a study by Karn et al(2020) in Nepal researched the knowledge and perception of coronavirus in different demographics, ethnicities, education, and area groups. The information was disseminated through news, online media, Viber, Facebook, and government websites (Karn et al, 2020).…”
Section: Application Of Social Marketing MIX Strategies During the Co...mentioning
confidence: 99%
See 2 more Smart Citations
“…A comparative study conducted in 2020 among the general population in Saudi Arabia, Egypt, and Jordan found that the perception of COVID-19 was significantly higher among the participants from Saudi Arabia and the perception of susceptibility to COVID-19 among the Saudi Arabians was also scored highly compared to Egypt and Jordan (Shahin & Hussien, 2020). Several researchers have illustrated that most people whether from developing countries like Nepal or developed countries like the USA and UK are highly fearful of the outbreak (Karn et al, 2020). A study conducted on risk perception towards the COVID-19 and its associated factors among waiters in selected towns of Southwest Ethiopia had a more excellent risk perception of the COVID-19, and this risk perception was also related to age (Asefa et al, 2020).…”
Section: Discussionmentioning
confidence: 99%